Seed priming for improving germination of sunflower (Helianthus annuus L.) at low temperature: SUNFLOWER GERMINATION AT LOW TEMPERATURE WITH DIFFERENT SEED TREATMENT METHODS - LAKSHMI PRAYAGA; C SARADA; P LAKSHMAMMA (Journal of Oilseeds Research, 2017)
Seeds of two sunflower hybrids, KBSH-44 and PSH-1962 were subjected to different treatment methods viz., direct sowing, priming for 24 and 48 hours along with absolute control to enhance germination at low temperature. Differences were observed for germination at low temperature between hybrids and PSH-1962 showed higher germination at low temperature. Among the treatments, response to absolute control (25°C) and direct sowing was similar. Priming did not improve germination in any of the hybrids at 10 and 15°C. Increase in priming duration resulted in decreased germination. Inhibitory effect of priming was more in KBSH-44 than PSH-1962. None of the treatments studied were effective in enhancing germination at low temperature.